2002
DOI: 10.1094/phyto.2002.92.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Dispute the Existence of the Afro-Andean Group of the Bean Angular Leaf Spot Pathogen, Phaeoisariopsis griseola

Abstract: Coevolution of the angular leaf spot pathogen, Phaeoisariopsis griseola, with its common bean host has been demonstrated, and P. griseola isolates have been divided into Andean and Mesoamerican groups that correspond to defined bean gene pools. Recent characterization of P. griseola isolates from Africa has identified a group of isolates classified as Andean using random amplified polymorphic DNA (RAPD), but which are able to infect some Mesoamerican differential varieties. These isolates, designated Afro-Ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 35 publications
8
41
2
1
Order By: Relevance
“…The distribution of these two gene pools across bean growing regions show that 75% of the total Mesoamerican bean samples were collected from the Kagera region, while very few were collected from Rukwa (17%) and Mbeya (8%) (Figure 3). These results from Tanzania confirm previous findings indicating that both Andean and Mesoamerican beans are grown within some African countries (Wortmann et al, 1998;Mahuku et al, 2002). In Tanzania, it has been found that farmers grow both Andean and Mesoamerican beans and in most cases they mix the two together in the same plot of land as a strategy of risk management since some cultivars fail and others are tolerant to biotic and abiotic factors (Blair et al, 2010).…”
Section: Host Genotype Characterizationsupporting
confidence: 88%
See 4 more Smart Citations
“…The distribution of these two gene pools across bean growing regions show that 75% of the total Mesoamerican bean samples were collected from the Kagera region, while very few were collected from Rukwa (17%) and Mbeya (8%) (Figure 3). These results from Tanzania confirm previous findings indicating that both Andean and Mesoamerican beans are grown within some African countries (Wortmann et al, 1998;Mahuku et al, 2002). In Tanzania, it has been found that farmers grow both Andean and Mesoamerican beans and in most cases they mix the two together in the same plot of land as a strategy of risk management since some cultivars fail and others are tolerant to biotic and abiotic factors (Blair et al, 2010).…”
Section: Host Genotype Characterizationsupporting
confidence: 88%
“…Because Andean isolates that were virulent on Mesoamerican genotypes were found, this suggests that in Tanzania, both common bean genetic backgrounds need to be improved so as to attain durable resistance. Similar findings have been reported from pathogenic characterization using differential cultivars (Ddamulira et al, 2014); however, in this study, no differential cultivars were used and instead virulence grouping was employed as described by Mahuku et al (2002) in which the affected genotypes were characterized. Further, in this study, there is interaction between Andean isolates with Mesoamerican genotypes where some Andean isolates were shown to be virulent on Mesoamerican genotypes ( Figure 5).…”
Section: Relationships Between Genotype and Pathogensupporting
confidence: 75%
See 3 more Smart Citations